IMPORTANCE OF PUBLICISTIC STYLE IN LANGUAGE DEVELOPMENT - Muqaddas Isroil (Journal Park Publishing, 2023)
Predominance of extra-linguistic factors in the development of language actually shows the influence of a person, the society he belongs to, on the language, and naturally, none of the external factors exist outside of the person, the society he belongs to. The language of journalism, which is always in step with the life of the society, has been rich in linguistic renewal and additions. The journalistic picture of the world created by the specific linguistic and non-linguistic features of mass media has a stronger impact than other types of world models and serves as an important factor in language development.